Naeem Hamid as Baydil’s Translator - Mustafa, Kashif; Kausar, Safia; Razzaq, Shireen (sourcecoder, 2022)
Naeem Al-Hamid is a well-known poet in Saudi Arabia. But in the world of Urdu, he is best known for his creative, plain and coherent translation of Baydil’s Persian poetry in Urdu. Following the top-notch rules of Urdu translation we find many examples of translated verses in poetic and prosaic manner. Abdul Kadar Baydil’s is known poet of Hindi diction whose thought and theme have impressed the great poets of India. But while the commoner Indians are not familiar with the Persian language so Hamid’s such contribution played a vital role in understanding the Persian poetry.